Spiritual Well-Being Of Post-Stroke Patients In Neurological Polyclinic of Al Ihsan Regional Public Hospital, West Java Province - Mulyani, Tita; Widianti, Efri; Mirwanti, Ristina (JURNAL PENDIDIKAN KEPERAWATAN INDONESIA, 2018)
ABSTRAK Stroke fase rehabilitasi dapat mengakibatkan perubahan fisik dan psikologis sehingga mempengaruhi kualitas hidup pasien yang kemudian menyebabkan masalah psikosial berupa cemas dan depresi. Cemas dan depresi ini memiliki korelasi terhadap kesejahteraan spiritual. Tujuan dari penelitian ini adalah untuk mengidentifikasi tingkat kesejahteraan spiritual  pada pasien pasca stroke di poliklinik RSUD Al Ihsan Provinsi Jawa Barat. Penelitian ini merupakan penelitian deskriptif kuantitatif dengan menggunakan instrumen SIWB. Penarikan sampel menggunakan metode purposive sampling dengan kriteria insklusi pasien stroke fase rehabilitasi yang mempunyai nilai Mini Mental State Examination (MMSE) normal 24-30, dan didapatkan 105 responden. Data disajikan dalam bentuk distribusi frekuensi. Hasil penelitian ini menunjukkan tingkat kesejahteraan spiritual tinggi sebanyak 57 responden (54,3%) dan tingkat kesejahteraan spiritual rendah sebanyak 48 responden (45,7%). Karakteristik responden paling banyak pada rentang usia lansia akhir yaitu berjumlah 41 responden (39,0%), dengan lama stroke 12 bulan 58 responden (55,2%), memiliki penyakit penyerta 82 responden (78,1%), dan mengalami serangan stroke 1x sebanyak 54 responden (51,4%). Pada penelitian ini, antara tingkat kesejahteraan spiritual tinggi dan rendah tidak jauh berbeda persentasenya. Sehingga  masih diperlukan upaya untuk meningkatakan kesejahteraan spiritual melalui perbaikan sarana dan prasaran ibadah ,mengoptimalkan spiritual care, mengadakan seminar-seminar dan pelatihan spiritual care, melakukan berdo’a bersama sebelum pemeriksaan dimulai, menciptakan lingkungan yang nyaman, aman, dan damai, serta mengadakan peer group khusus pasien stroke. ABSRTACTStroke rehabilitation phase can lead to physical and psychological changes. It has an impact on the quality of life of patients that later caused psychosocial problems such as anxiety and depression. These anxiety and depression have a correlation to the spiritual well-being. The purpose of this study was to identify the level of spiritual well-being in post-stroke patients in polyclinic RSUD Al Ihsan West Java Province. This research was a quantitative descriptive research using SIWB instruments. It used a purposive sampling method with the inclusion criteria of rehabilitation phase stroke patients who had 24-30 as the normal score of Million Minimum State Examination (MMSE) and obtained 105 respondents. The data presented in the form of the frequency distribution. The results of this study indicated that the respondent’s amount who reached the high level of spiritual well-being was 57 respondents (54.3%) and low level of spiritual well-being was 48 respondents (45.7%). The most respondents’ characteristic were respondents with age range of elderly as of 41 respondents (39.0%), with stroke length more than 12 months as of 58 respondents (55.2%), had comorbid disease as of 82 respondents (78.1%), and suffered once stroke attack as of 54 respondents (51.4%). The research revealed that the percentage level of spiritual well-being between high and low was nearly similar. As the consequences, it is necessary to increase the spiritual well-being through the improvement of religious facilities and infrastructure, optimizing spiritual care, conducting seminars and spiritual care training, praying together before the medical check-up or treatment, creating a comfortable, safe and peaceful environment, and establish the peer group for stroke patients.